Maternal diet and human milk composition: an updated systematic review - Petersohn, Inga; Hellinga, Anneke H.; van Lee, Linde; Keukens, Nicole; Bont, Louis; Hettinga, Kasper A.; Feskens, Edith J. M.; Brouwer-Brolsma, Elske M. (Frontiers in Nutrition, 2024)
Context Exclusive breastfeeding for 6 months after birth provides infants with the best start for life. A review by Bravi et al. summarized the importance of maternal diet as a determinant of human milk composition based on data up to 2015, but evidence on nutrient intake level was limited. Objective We updated the review by Bravi et al., critically assessed differences in study designs and sampling methods, and graphically visualized trends and associations. Data sources PubMed was systematically searched for articles published between January 2015 and March 2021. Data extraction Article screening, selection, and data extraction was done by two independent researchers, including a risk of bias assessment based on 11 criteria. Articles were eligible when including: quantitative information, commonly used effect estimates, healthy mother-infant dyads. Results Twenty seven observational and five intervention studies were identified (n = 7,138) and combined with results of Bravi et al. Fatty acids were still the most studied human milk components in relation to maternal diet (n = 17 studies) with maternal fish intake being predominantly positively associated with milk ALA (r = 0.28–0.42), DHA (r = 0.24–0.46), and EPA (r = 0.25–0.28) content. PUFAs from diet were generally positively correlated with their concentrations in milk, while SFA intake was negatively associated with several fatty acids in milk. Studies on associations with maternal diet and milk carbohydrates, proteins, vitamins and minerals were limited in number and varied in methods and results. Conclusion This updated review shows that evidence on the association between maternal diet and human milk fatty acids is rapidly increasing, but still diversified in methodology and results. Further studies, preferably intervention studies, assessing diet and milk carbohydrates, proteins, vitamins and minerals are needed to be able draw conclusions on the importance of maternal diet for human milk composition as a whole.